Zinc Status in South Asian PopulationsAn Update (Journal of Health, Population and Nutrition, 2013)
This article attempts to highlight the prevalence of zinc deficiency and its health and economic consequences in South Asian developing countries and to shed light on possible approaches to combating zinc deficiency. A computer-based search was performed on PubMed, Google, and ScienceDirect.com to retrieve relevant scientific literature published between 2000 and 2012. The search yielded 194 articles, of which 71 were culled. Studies were further screened on the basis of population groups, age and sex, pregnancy, and lactation. The most relevant articles were included in the review. Cutoffs for serum zinc concentration defined for zinc deficiency were 65 ?g/dL for males and females aged